Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.